Acoustic induced flow around an evaporating drop and its influence on internal circulation. (July 2019) - Prasad, Suraj; Narayanan, S.; Mandal, Deepak Kumar
Highlights: Acoustic field influences the internal circulation of evaporating drops. Higher circulation is observed when a drop is subjected to acoustic frequency. The reason is the formation of acoustic boundary layer around the drop. The layer entrains the air around the drop, and thereby enhances the circulation. Abstract: The present study provides a detailed investigation on the internal circulation of evaporating methanol and water drops in presence of an acoustic field. The drops are suspended inside an anechoic chamber, and the internal circulation of the drop with and without the acoustic field, is recorded to determine the effect of the acoustic field on the circulation. A sine wave of different frequencies and constant amplitude, with and without added white noise, is used for generating the acoustic field. The presence of the field is observed to significantly influence the circulation. Higher circulation is observed when a drop is subjected to acoustic frequency. For a given acoustic frequency, the presence of white noise enhances the circulation and hence the evaporation, compared to its absence. Maximum steady circulation is observed at 30 Hz, following which the average velocity of circulation decreases with increasing acoustic frequency. The reason for the increased circulation as well as the evaporation in presence of the acoustic field is due to the formation of an acoustic boundary layer around the evaporating drop. The presence of the layer causes higher entrainment of the surrounding air around the drop surface and thus enhances the circulation and the evaporation. The thickness of the layer determines the region subjected to motion due to acoustic waves around the drop. The present study reveals that higher effective streaming velocity is pronounced at smaller acoustic boundary layer thickness, and leads to the enhancement in the circulation as well as the evaporation. The thickness is observed to be minimum at 30 Hz and increases with the acoustic frequency, whereas, the effective streaming velocity is maximum at 30 Hz and reduces as the frequency increases. Graphical abstract: Image, graphical abstract